Raw Material Blend Optimization : Case Company Operating in Process Industry - Rintala, Hanna (My University, 2020)
Raw material costs represent a significant amount of products’ value in manufacturing companies. In the process industry, the production is based on a continuous flow and raw material recipes. The production machines are generally inflexible and the fixed costs are high, which is why cost advantages can be achieved by maximizing productivity or minimizing interruptions and variable costs. Optimal use of resources is a way to minimize costs and to bring value to the customer, which is why recipes, that specify the use of raw materials in different products, are in the focus of the thesis. The aim is to provide information about optimal raw material recipes and cost-effective raw material procurement in process industry. The thesis employs mixed-methods approach and a case study. Qualitative approach is used to study the market uncertainties related raw material supply; which includes e.g. raw material availabilities, prices and yield coefficients. Four qualitative scenarios are created as inputs for the quantitative part that studies the blending problem in a case company. Nonlinear programming is applied and the objective is to minimize the costs related to raw material, which in addition to the purchase price and freight, includes the costs that arise from material loss in the production. It is noticed in the study that even a little decrease in the raw material yield can cause significant costs annually. Performance-based (PBC) and behavior-based supply contracts are discussed in order to assure a stable or even better level on raw material quality. It is recommended that the buyer could either pay incentives for better raw material quality, or participate in suppliers’ quality enhancing investments. It should be investigated if it is more cost-effective to cooperate with the supplier or to invest in the mill’s own equipment to improve the raw material quality. If the buyer decides on using PBC, based on the fact that in the process industry the product being processed is not visible for the operators and it is hard to measure what is happening inside the production line, it is recommended that input and output quantities are used as performance indicators over outcome-based measurement. In the end, the buyer should consider its operational performance objectives and choose the contracting method accordingly. This case study provides an example of how qualitative scenarios and nonlinear programming can be of use in the production planning and contract management on a tactical level.

Prosessiteollisuudessa raaka-ainekustannukset vastaavat merkittävästä osuudesta lopputuotteiden kustannuksessa ja valmistus perustuu raaka-aineresepteihin. Tuotantolaitteet ovat pääasiassa kankeita ja joustamattomia, ja kiinteät kustannukset ovat korkeat. Siksi kustannusetua voidaan tavoitella maksimoimalla tuottavuutta ja minimoimalla häiriöitä ja muuttuvia kustannuksia. Optimaalinen resurssien käyttö on tapa minimoida kustan-nuksia ja tuoda arvoa asiakkaalle, minkä takia raaka-ainereseptien optimointi on tämän tutkielman keskiössä. Tavoite on luoda optimointityökalu case-yritykselle, ja sitä kautta johtaa tietoa myös hankinnan osa-alueelle sopimushallintaan liittyen sekä yritykselle että akateemiseen keskusteluun. Tutkielma soveltaa case-tutkimukseen monimenetelmällistä tutkimusotetta, jossa kvalitatiivisesti luodaan skenaarioita kuvastamaan markkinoiden epävarmuutta, joka tässä tilanteessa liittyy pääasiassa ostohinnan vaihteluun, raaka-aineiden saatavuuteen ja raaka-aineen laatuun liittyvään saantoprosenttiin. Kvantitatiivisessa osiossa raaka-ainereseptiin sovelletaan epälineaarista optimointimenetelmää, jonka tavoite on minimoida raaka-ainekustannukset sisältäen raaka-aineen ostohinnan, logistiikkakustannukset ja huonosta laadusta aiheutuvan sivuvirran kustannukset. Tutkielma osoittaa, että pienikin vähentyminen raaka-ainesaantoprosentissa aiheuttaa vuositasolla merkittäviä kustannuksia, minkä takia raaka-ainelaatuun suositellaan kiinnittämään huomiota sopimustasolla. Suorituskykyyn perustuva toimittajien palkitseminen (performance-based contracting, PBC) on eräs vaihtoehto raaka-aineen laadun parantamiseksi. Ottaen huomioon, että prosessiteollisuudessa tuotteiden ja prosessien mittaaminen tuotantoprosessin aikana on hankalaa, panosten laatu on suositeltavampi suorituskyvyn mittari kuin lopputuloksen mittaaminen. Lisäksi sopimusmuoto tulisi valita organisaation operationaalisten tavoitteiden mukaan. Organisaation on myös hyvä tutkia, onko kannattavampaa panostaa laadun parantamiseen yhteistyössä toimittajien kanssa, vai panostaa omiin tuotantolaitteisiin saannon parantamiseksi. Tutkielma tarjoaa esimerkin, miten kvalitatiiviset skenaariot yhdessä epälineaarisen optimoinnin kanssa sopivat tuotannon ja hankinnan tueksi keskipitkän aikavälin suunnitteluun epävarmuus-tekijöiden tarkastelussa. Tulevaisuudessa tutkimuksessa voisi keskittyä prosessiteollisuuden ominaispiirteet huomioon ottavan kokonaisvaltaisen sopimusviitekehyksen luomiseen PBC:n alueella.
Keywords: Raw material costs, blending problem, optimization, scenarios, contract management